BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Insect catch at historic libraries in rural and urban settings - Peter Brimblecombe; Ute Rohrer; Bill Landsberger; Pascal Querner (International Biodeterioration & Biodegradation, 2024)

No indication of methodological biases in tullgren and macfadyen extraction of edaphic microarthropods - Alexander Bruckner; Pascal Querner; Cornelia Scholz (European Journal of Soil Biology, 2023)

Commercial glyphosate-based herbicides effects on springtails (Collembola) differ from those of their respective active ingredients and vary with soil organic matter content - Michael Maderthaner; Maureen Weber; Eszter Takács; Mária Mörtl; Friedrich Leisch; Jörg Römbke; Pascal Querner; Ronnie Walcher; Edith Gruber; András Székács; Johann G. Zaller (Environmental Science and Pollution Research, 2020)
Glyphosate-based herbicides (GBH) are currently the most widely used agrochemicals for weed control. Environmental risk assessments (ERA) on nontarget organisms mostly consider the active ingredients (AIs) of these herbicides, while much less is known on effects of commercial GBH formulations that are actually applied in the field. Moreover, it is largely unknown to what extent different soil characteristics alter potential side effects of herbicides. We conducted a greenhouse experiment growing a model weed population of Amaranthus retroflexus in arable field soil with either 3.0 or 4.1% soil organic matter (SOM) content and treated these weeds either with GBHs (Roundup LB Plus, Touchdown Quattro, Roundup PowerFlex) or their respective AIs (isopropylammonium, diammonium or potassium salts of glyphosate) at recommended dosages. Control pots were mechanically weeded. Nontarget effects were assessed on the surface activity of the springtail species Sminthurinus niger (pitfall trapping) and litter decomposition in the soil (teabag approach). Both GBHs and AIs increased the surface activity of springtails compared to control pots; springtail activity was higher under GBHs than under corresponding AIs. Stimulation of springtail activity was much higher in soil with higher SOM content than with low SOM content (significant treatment x SOM interaction). Litter decomposition was unaffected by GBHs, AIs or SOM levels. We suggest that ERAs for pesticides should be performed with actually applied herbicides rather than only on AIs and should also consider influences of different soil properties.

Effects of vineyard inter-row management on the diversity and abundance of plants and surface-dwelling invertebrates in Central Romania - Cristina Fiera; Werner Ulrich; Daniela Popescu; Claudiu-Ioan Bunea; Minodora Manu; Ioana Nae; Melania Stan; Bálint Markó; István Urák; Andrei Giurginca; Nicole Penke; Silvia Winter; et al. (Journal of Insect Conservation, 2020)
Vineyard inter-rows are important biodiversity hotspots within agricultural landscapes, especially when they are covered with vegetation. However, little is known on the effects to management intensity on a broad range of surface-dwelling invertebrates and their interaction with vegetation. We assessed the diversity and activity density of ants, beetles, millipedes, mites, spiders, springtails and woodlice using pitfall traps in vineyards with either high management intensity (HI) consisting of frequently tilled inter-rows or low management intensity (LO) with alternating tillage in every second inter-row. The study was performed in the Târnave wine region in Central Romania. We wanted to know whether, (i) vineyard management intensity affects the diversity of plants and invertebrates, and (ii) local habitat characteristics affect species richness of different functional guilds and taxa. Species richness of some invertebrate taxa (Coleoptera, Araneae, Formicidae) did significantly differ between HI and LO vineyards. Only phytophages (some Coleoptera) increased in species richness and activity density with vegetation cover. Vineyard soil properties (organic matter content, pH, P, and K) did not significantly differ between HI and LO vineyards. We conclude that vineyard inter-row management can affect both the conservation of biodiversity and the provision of biodiversity-driven ecosystem services.